The Qur'anic pagans and related matters - Crone, Patricia, 1945-2015.
1 online resource.
Keywords: Patricia Crone's Collected Studies in Three Volumes brings together a number of her published, unpublished, and revised writings on Near Eastern and Islamic history, arranged around three distinct but interconnected themes. Volume 1, The Qurʾānic Pagans and Related Matters , pursues the reconstruction of the religious environment in which Islam arose and develops an intertextual approach to studying the Qurʾānic religious milieu. Volume 2, The Iranian Reception of Islam: The Non-Traditionalist Strands , examines the reception of pre-Islamic legacies in Islam, above all that of the Iranians. Volume 3, Islam, the Ancient Near East and Varieties of Godlessness , places the rise of Islam in the context of the ancient Near East and investigates sceptical and subversive ideas in the Islamic world. The Iranian Reception of Islam: The Non-Traditionalist Strands Islam, the Ancient Near East and Varieties of Godlessness